A controversial case of pigmentary mosaicism along Blaschko’s lines with neurological impairment. - Schepis, C.; Siragusa, M.; Romano, C. (European Journal of Pediatric Dermatology, 2009)
We describe here a sporadic case of pigmentary mosaicism distributed along the Blaschko’s lines in a 10-year-old mentally retarded girl. She showed two different skin colors: hyperpigmented and hypopigmented lesions arranged in streaks and whorls. Only a few similar cases have been reported.